The effect of induction of CYP3A4 by St John's Wort on ambrisentan plasma pharmacokinetics in volunteers of known CYP2C19 genotype - Markert, Christoph; Kastner, Ida Maria; Hellwig, Regina; Schweizer, Yvonne; Burhenne, Jürgen; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E. (Basic & clinical pharmacology & toxicology, 2015)
To evaluate the impact of CYP2C19 polymorphisms on ambrisentan exposure and to assess its modification by St. John's wort (SJW), 20 healthy volunteers (10 CYP2C19 extensive, four poor and six ultrarapid metabolizers) received therapeutic doses of ambrisentan (5 mg qd po) for 20 days and concomitantly SJW (300 mg tid po) for the last 10 days. To quantify changes of CYP3A4 activity, midazolam (3 mg po) as a probe drug was used. Ambrisentan pharmacokinetics was assessed on days 1, 10 and 20, and midazolam pharmacokinetics before and on days 1, 10, 17 and 20. At steady state, ambrisentan exposure was similar in extensive and ultrarapid metabolizers but 43% larger in poor metabolizers (p < 0.01). In all volunteers, SJW reduced ambrisentan exposure and the relative change (17-26%) was similar in all genotype groups. The extent of this interaction did not correlate with the changes in CYP3A activity (midazolam clearance) (rs = 0.23, p = 0.34). Ambrisentan had no effect on midazolam pharmacokinetics. In conclusion, SJW significantly reduced exposure with ambrisentan irrespective of the CYP2C19 genotype. The extent of this interaction was small and thus likely without clinical relevance.